Optimum performance of rotor blade with different airfoil for Primus Wind power AIR 40 Wind Turbine 12VDC - Tahaa, Hawraz .O.; .M. Al-Hamookab, Iyd Eqqab (Anbar Journal of Engineering Sciences, 2021)
The increasing price of fossil derivatives, global warming and energy market instabilities are a major problem. In recent years, these problems led to an increasing using of renewable energy sources such as wind energy. Wind turbine used to extract this energy from the wind to produce power or electricity. Due to low cost, easy for maintenance and it is, portability the most com-monly used among wind turbines is small axis wind turbine. Analysis to optimization power coef-ficient ( ) of a small wind turbine blade design model (Primus Wind power AIR 40 Wind Tur-bine 12VDC) are evaluated and discussed in this study. A shape of blade wind turbine is the pri-mery parapeter affected the power output of wind turbine. In this type of turbine NACA2411 used as the blade airfoil as represent shape of blade. For this goal, 185 different airfoils selected. For this purpose, using the XFOIL software to simulate the properties of each airfoil at Re (1.0*105, 1.5*105, 2.0*105, 2.5*105, 3.0*105 and 3.5*105) and angle of attack from 0˚ to 10˚, Then elimination criteria was performed for removing those airfoils would not suitable for the purpose up on their effiency. At the end of analysing Matlab software used for calculate the power coeffi-cient and selecting the best airfoils design for used manufacture anew blade for that type of small wind turbine with better power coefficient. The output of XFOIL and matlab software showed by tabulates and graphs. As a results show 3 airfoils were selected due to their performance better than other airfoils from an initial group of 185 as exemplification of the methodology namely S1210,SD7034 and S2091, The maximum that has been achieved by which used airfoil S1210 equal to 0.52 at Re 350000.